Techquest: guia de verbetes da comunicação disruptiva do século XXI - Boarini, Dulce Margareth (2020)
This doctoral thesis aimed to elaborate the “techquest: Guide to the entry of disruptive communication in the 21st century”, an unprecedented and contributory tool in the formation of the repertoire of the professional of organizational communication. The guide includes contextualized entries of inter and multidisciplinar themes. The main characteristics of the “techquest” are centered on the curatorial process of production, ease to be updated and easy access. The guide emerges in the context of what we define the second disruptive wave in communication, understanding the confluence between big data, artificial intelligence and internet of things, and their impacts in the communication sphere. The first wave took place with the consolidation of social media, starting in the 2000s. The thesis comprises two bodies, divided into four chapters (historical and communicational contexts, interview with executives, presentation to the guide) and the entry guide, a multidisciplinary doctoral product. The methodology used was based on a qualitative, exploratory nature, with a focus on documental and bibliographic research and on investigative in depth with organizational communication professionals